A Phenomenology of Students' Perception of Feminist Issues: Discourse Analysis of Social Science 105 Journals - Lanuza, Gerry M. (Review of Women's Studies; Vol 14 No 1 (2004): Review of Women's Studies Volume XIV, Number 1 (January-June 2004))
In teaching Social Science 105, Gender Issues in Philippine Society, this professor asked his students to write regularly in journals their own ideas on certain topics that he assigned. The following study is based on his analysis of the entries on these journals. What he did is to provide an analysis of these discourses. His approach is anecdotal, but it shows how students feel or think about issues on violence, sexuality, and gender relations.